Tracing the Maritime Greatness and the Formation of the Cosmopolitan Society in South Borneo - Yety Rochwulaningsih; Noor Naelil Masruroh; Fanada Sholihah (Diponegoro University, 2019)
This article examines the triumph of the maritime world of South Borneo and the construction of a cosmopolitan society as a result of the trade diaspora and the mobility of nations from various regions. A “liquid” situation has placed Banjarmasin as a maritime emporium in the archipelago which influenced in the 17th century. In fact, the expansion of Islam in the 16th to 17th centuries in Southeast Asia directly impacted the strengthening of the existing emporium. Thus, for a long time, Banjarmasin people have interacted and even integrated with various types of outsiders who came, for example, Javanese, Malays, Indians, Bugis, Chinese, Persians, Arabs, British and Dutch. In the context of the maritime world, the people of South Borneo are not only objects of the entry of foreign traders, but are able to become important subjects in trading activities, especially in the pepper trade. The Banjar Sultanate was even able to respond to the needs of pepper at the global level through intensification of pepper cultivation. As a pepper trade emporium. The Banjar Sultanate often faced the threat of piracy, especially in the mid-19th century, one of which was masterminded by the Bugis and Ilanun pirates. This paper will further discuss how the triumph of the maritime world of South Borneo and the construction of a cosmopolitan society as a result of the dynamic maritime activities in South Borneo? Learning from these historical facts, it is important for South Borneo to revitalize and reorient how to make the maritime economy a foothold for making progressive changes.